Endovascular treatment in bilateral cavernous sinus dural arteriovenous fistulas: a systematic review and meta-analysis - Pang-Shuo Perng; Yu Chang; Yuan-Ting Sun; Hao-Kuang Wang; Yu-Shu Jiang; Jung-Shun Lee; Liang-Chao Wang; Chih-Yuan Huang (Scientific Reports, 2023)
Abstract Few studies have discussed the disease nature and treatment outcomes for bilateral cavernous sinus dural arteriovenous fistula (CSDAVF). This study aimed to investigate the clinical features and treatment outcomes of bilateral CSDAVF. Embase, Medline, and Cochrane library were searched for studies that specified the outcomes of bilateral CSDAVF from inception to April 2022. The classification, clinical presentation, angiographic feature, surgical approach, and treatment outcomes were collected. Meta-analysis was performed using the random effects model. Eight studies reporting 97 patients were included. The clinical presentation was mainly orbital (n = 80), cavernous (n = 52) and cerebral (n = 5) symptoms. The most approached surgical route was inferior petrosal sinus (n = 80), followed by superior orbital vein (n = 10), and alternative approach (n = 7). Clinical symptoms of 88% of the patients (95% CI 80–93%, I2 = 0%) were cured, and 82% (95% CI 70–90%, I2 = 7%) had angiographic complete obliteration of fistulas during follow up. The overall complication rate was 18% (95% CI 11–27%, I2 = 0%). Therefore, endovascular treatment is an effective treatment for bilateral CSDAVF regarding clinical or angiographic outcomes. However, detailed evaluation of preoperative images and comprehensive surgical planning of the approach route are mandatory owing to complexity of the lesions.